Terahertz-Field-Induced Time Shifts in Atomic Photoemission - Schmid, Georg; Schnorr, Kirsten; Augustin, Sven; Meister, Severin; Lindenblatt, Hannes; Trost, Florian; Liu, Yifan; Stojanovic, Nikola; Al-Shemmary, Alaa; Golz, Torsten; Treusch, Rolf; Gensch, Michael; et al. (My University, 2019)
Time delays for atomic photoemission obtained in streaking or reconstruction of attosecond bursts by interference of two-photon transitions experiments originate from a combination of the quantum mechanical Wigner time and the Coulomb-laser coupling. While the former was investigated intensively theoretically as well as experimentally, the latter attracted less interest in experiments and has mostly been subject to calculations. Here, we present a measurement of the Coulomb-laser coupling-induced time shifts in photoionization of neon at 59.4 eV using a terahertz (THz) streaking field (λ=152 μm). Employing a reaction microscope at the THz beamline of the free-electron laser in Hamburg (FLASH), we have measured relative time shifts of up to 70 fs between the emission of 2p photoelectrons (∼38 eV) and low-energetic (<1 eV) photoelectrons. A comparison with theoretical predictions on Coulomb-laser coupling reveals reasonably good agreement.